2020
DOI: 10.1111/jgs.16427
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Screening, Triage Urgency, and 30‐Day Mortality in Older Emergency Department Patients

Abstract: BACKGROUND Urgency triage in the emergency department (ED) is important for early identification of potentially lethal conditions and extensive resource utilization. However, in older patients, urgency triage systems could be improved by taking geriatric vulnerability into account. We investigated the association of geriatric vulnerability screening in addition to triage urgency levels with 30‐day mortality in older ED patients. DESIGN Secondary analysis of the observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 45 publications
(99 reference statements)
1
51
0
1
Order By: Relevance
“…Previous studies suggested that geriatric screening tools have the potential to refine the prognostic performance of routine assessments in acute care settings [ 10 , 27 ]. Similar to what we now report, these studies have shown that the combination of measures of illness acuity and vulnerability can better explain the variability of adverse outcomes in acutely ill older patients [ 10 , 27 , 28 ]. For example, Blomaard et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies suggested that geriatric screening tools have the potential to refine the prognostic performance of routine assessments in acute care settings [ 10 , 27 ]. Similar to what we now report, these studies have shown that the combination of measures of illness acuity and vulnerability can better explain the variability of adverse outcomes in acutely ill older patients [ 10 , 27 , 28 ]. For example, Blomaard et al .…”
Section: Discussionmentioning
confidence: 99%
“…That is unfortunate, as multiple factors possibly increase the older adults’ risk of experiencing complications from COVID-19, including physiological changes that affect vital signs (e.g. absence of fever), multimorbidity, cognitive impairment, sensory deficits and atypical presentations of disease [ 9 , 10 ]. Because conventional screening tools often fail to capture the key elements of risk in older persons (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, 30-day mortality after ED visit is more associated with frailty than triage urgency. (38) As such, caregiver burden may be a marker of system frailty (as opposed to individual frailty).…”
Section: Discussionmentioning
confidence: 99%